Future Circular Collider beam screen: progress on Tl-1223 HTS coating. (6th April 2020) - Leveratto, A; Saba, A; Holleis, S; Himmerlich, M; Henrist, B; Fernandez-Peña, S; Moros, A; Bernardi, J; Eisterer, M; Bernini, C; Vaglio, R; Putti, M; et al.
Abstract: Thallium-1223, a superconductor with high critical temperature ( T c ∼ 120 K) and high irreversibility line is a promising alternative to copper layers as a low surface impedance material in particle accelerator components. In the existing design of the Future Circular Collider (FCC-hh), for reasons of cryogenic efficiency and vacuum stability, the beam screen that shields the dipoles from synchrotron radiation has to stay at best in the temperature range between 40 and 60 K, in which copper surface resistance might be too high to prevent beam instabilities due to wakefields. This paper reports the progress on the realization of thallium-1223 based high temperature superconducting (HTS) coatings realized by electrochemical deposition. The study of the Tl-1223 phase has been carried out on precursor-pellets and films. Transport characterization revealing a very high irreversibility line and also high local critical currents obtained from Scanning Hall Probe Microscopy (SHPM) measurements will be shown. A first analysis of compatibility in vacuum has been carried out and the generation of secondary electrons (SEY) has been investigated as well. The encouraging results, although not conclusive, will state that thallium-based phase could be suitable for the proposed application.